Intellectual Property Rights : A Critical History - May, Christopher; Sell, Susan K. (iPolitics: Global Challenges in the Information Age, 2022)
With intellectual property widely acknowledged today as a key component of economic development, those accused of stealing knowledge and information are also charged with undermining industrial innovation, artistic creativity, and the availability of information itself. How valid are these claims? Has the Trade Related Aspects of Intellectual Property Rights (TRIPs) Agreement ushered in a new, better era? Christopher May and Susan Sell trace the history of social conflict and political machinations surrounding the making of property out of knowledge. Ranging from ancient commerce in Greek poems to present-day controversies about online piracy and the availability of AIDS drugs in the poorest countries, May and Sell present intellectual property law as a continuing process in which particular conceptions of rights and duties are institutionalized; each settlement prompts new disputes, policy shifts, and new disputes again. They also examine the post-TRIPs era in the context of this process. Their account of two thousand years of technological advances, legal innovation, and philosophical arguments about the character of knowledge production suggests that the future of intellectual property law will be as contested as its past.